The Cinema of Attractions Reloaded - Strauven, Wanda (Film Culture in Transition, 2006)
What have Lumière in common with Wachowski? More than one hundred years separate these two pairs of brothers who astonished, quite similarly, the film spectator of their respective time with special effects of movement: a train rushing into the audience and a bullet flying in slow motion. Do they belong to the same family of "cinema of attractions"? Twenty years ago Tom Gunning introduced the phrase "cinema of attractions" to define the essence of the earliest films made between 1895 and 1906. His term scored an immediate success, even outside the field of early cinema. The present anthology questions the attractiveness and usefulness of the term for both pre-classical and post-classical cinema. With contributions by the most prominent scholars of this discipline (such as Tom Gunning, André Gaudreault, Thomas Elsaesser, Charles Musser, Scott Bukatman and Vivian Sobchack) this volume offers a kaleidoscopic overview of an important historiographical debate.